Sentiment Analysis on Reviews of Pancasila Park Tourist Attraction in Tegal City Using the Naive Bayes Method - Jiwangga, Alifah Tembang; Ramdhan, Nur Ariesanto; Hamid, Abdul; Premana, Agyztia; Bhakti, R.M. Herdian (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to analyze the sentiment of reviews of Tegal City Pancasila Park using the Naive Bayes method. The data collection method used is by crawling review data on the Google Review site and literature studies. The data that is ready will be subjected to a sentiment analysis process using the rapidminner application. Previously, the data will go through a cleaning process, namely removing unimportant attributes. This process includes cleaning, tokenizing, removing stopward, transforming case. The results of this study indicate that the naive bayes method can learn the existing training data well. The accuracy level of this method is 100%. The true positive value is 234. While the positive data that is considered negative (false negative) is 28 data. The accuracy of this naive bayes method is quite high because the researcher uses the replace missing values method. The amount of data also affects the results of the classification method test. 3. The conclusion of this sentiment proves that the public gives more positive comments on the review of Pancasila Park in Tegal City which has been proven by review analysis using the naive Bayes method based on the Rapidminer application.